Pendampingan Pengolahan Pempek Lele Sebagai Alternatif Usaha Masyarakat Di Desa Sampora - Mulyadi, Melisa -; Ghozali, Theresia (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2022)
Cultivation of catfish carried out by the people of Sampora Village is certainly expected to improve the welfare of the community. It takes creativity from the community to increase the economic value of catfish through diversification of food products made from catfish, including catfish pempek. So far, people mostly use belida fish, mackerel or gabus fish as ingredients for pempek, but it turns out that catfish can also be processed into pempek because it has soft and white flesh like belida fish. Catfish besides containing high nutrition is also cheaper than other fish. If it can be producing quality catfish pempek, of course, catfish pempek can attract people to consume it because the price is more affordable. The final product of pempek is determined by its white color, elasticity, aroma and taste. There are several types of pempek that can be produced, namely pempek lenjer, pempek “keriting”, pempek “kapal selam” which contains eggs and can also be varied with sausage or cheese filling. The assistance carried out aims to equip the Sampora village community with the skills to process catfish into pempek so that it can be used as an alternative business.